2019
DOI: 10.21203/rs.2.11513/v4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

MEG3 promotes proliferation and inhibits apoptosis in osteoarthritis chondrocytes by miR-361-5p/FOXO1 axis

Abstract: Background: This study aimed to investigate the role of long non-coding RNA (lncRNA) maternally expressed 3 (MEG3) and related molecular mechanisms in osteoarthritis (OA). Methods: Patients with OA and patients undergoing thigh amputation were involved in OA group and normal group, respectively. Cartilage tissues of all patients were isolated and cultured. Based on different transfection, MEG3 cells were grouped into Blank, pcDNA3.1-NC, pcDNA3.1-MEG3, si-NC, si-MEG3, pcDNA3.1-NC + mimics NC, pcDNA3.1-MEG3 + mi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Wang et al showed that MEG3 lncRNA is downregulated in the cartilage tissues of rats with OA. 37 Xu et al showed that the expression level of MEG3 is downregulated in OA tissues and is negatively correlated with VEGF expression, suggesting that MEG3 may participate in the pathologic processes of OA by regulating angiogenesis. 38 In our present study, the expression of DRG and MEG3 in the SDH of CFA-induced rats was significantly reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al showed that MEG3 lncRNA is downregulated in the cartilage tissues of rats with OA. 37 Xu et al showed that the expression level of MEG3 is downregulated in OA tissues and is negatively correlated with VEGF expression, suggesting that MEG3 may participate in the pathologic processes of OA by regulating angiogenesis. 38 In our present study, the expression of DRG and MEG3 in the SDH of CFA-induced rats was significantly reduced.…”
Section: Discussionmentioning
confidence: 99%